Comparative analysis of EZH2, p16 and p53 expression in uterine carcinosarcomas - Evelin Makk; Noémi Bohonyi; Angéla Oszter; Klára Éles; Tamás Tornóczky; Arnold Tóth; Endre Kálmán; Krisztina Kovács (Frontiers Media S.A., 2023)
Introduction: The role of p16 and p53 immunohistochemistry in the diagnosis of rare and aggressive uterine carcinosarcoma (UCS) has been well established. However, enhancer of zeste homolog 2 (EZH2), a histone methyltransferase and a member of the polycomb group family is a relatively new biomarker, with limited published data on its significance in this tumor type. The goal of this study was to examine EZH2 expression in UCS and its components, in correlation with morphological features, and p16 and p53 staining patterns.Methods: Twenty-eight UCSs were included in the study. EZH2, p16 and p53 immunoreactivity were assessed independently by two pathologists in both tumor components (epithelial and mesenchymal). EZH2 and p16 immunostains were scored semiquantitatively: based on the percentage and intensity of tumor cell staining a binary staining index ("high- or low-expressing") was calculated. The p53 staining pattern was evaluated as wild-type or aberrant (diffuse nuclear, null, or cytoplasmic expression). Statistical tests were used to evaluate the correlation between staining patterns for all three markers and the different tumor components and histotypes.Results: High EZH2 and p16 expression and aberrant p53 patterns were present in 89.3% 78.6% and 85.7% of the epithelial component and in 78.6%, 62.5% and 82.1% of the mesenchymal component, respectively. Differences among these expression rates were not found to be significant (p > 0.05). Regarding the epithelial component, aberrant p53 pattern was found to be significantly (p = 0.0474) more frequent in the serous (100%) than in endometrioid (66.6%) histotypes. Within the mesenchymal component, p53 null expression pattern occurred significantly (p = 0.0257) more frequently in heterologous sarcoma components (71.4%) compared to the homologous histotype (18.8%).Conclusion: In conclusion, EZH2, p16 and p53 seem to play a universal role in the pathogenesis of UCS; however, a distinctive pattern of p53 expression appears to exist between the serous and endometrioid carcinoma components and also between the homologous and heterologous sarcoma components.